1978
DOI: 10.2307/2530008
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Distributions and Size-Biased Sampling with Applications to Wildlife Populations and Human Families

Abstract: When an investlgator records an observation by nature according to a certain stochastic model the recorded observation will not have the original distribution unless everJ observation is given an equal chance of being recorded. A number of papers have appeared during the last ten years implicitly using the concepts of weighted and size-biased sampling distributions. In this paper we examine some general models leading to weighted distributiosls with weight functions not necessarily bounded by unity. The exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
255
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 448 publications
(258 citation statements)
references
References 5 publications
1
255
0
2
Order By: Relevance
“…Especially the weibull distribution and its generalizations in the literature attract the most of the researchers due to its wide range applications. The Weibull distribution includes the exponential and the Rayleigh distributions as sub models, the usefulness and applications of parametric distributions including Weibull, Rayleigh are seen in various areas including reliability, renewal theory, and branching processes which can be seen in papers by many authors such as in { [16], [17], [25]}. Different generalizations of the Weibull distribution are common in the literature as in { [4], [5], [21], [22], [28], [38]} and another generalization of the weibull distribution using the concept of weighted distributions is available as in { [6], [8], [19], [24], [30], [34], [36], [37]}.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the weibull distribution and its generalizations in the literature attract the most of the researchers due to its wide range applications. The Weibull distribution includes the exponential and the Rayleigh distributions as sub models, the usefulness and applications of parametric distributions including Weibull, Rayleigh are seen in various areas including reliability, renewal theory, and branching processes which can be seen in papers by many authors such as in { [16], [17], [25]}. Different generalizations of the Weibull distribution are common in the literature as in { [4], [5], [21], [22], [28], [38]} and another generalization of the weibull distribution using the concept of weighted distributions is available as in { [6], [8], [19], [24], [30], [34], [36], [37]}.…”
Section: Introductionmentioning
confidence: 99%
“…Weighted distributions are employed mainly in research associated with reliability, bio-medicine, meta-analysis, econometrics, survival analysis, renewal processes, physics, ecology and branching processes which are found in Patil and Rao (1978), Gupta and Kirmani (1990), Gupta and Keating (1985), Oluyede (1999), Patil and Ord (1976) and Zelen and Feinleib (1969). A weighted form of Rayleigh distribution has been published by Reshi et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Being first introduced by Rayleigh (1880), this statistical model was originally derived in connection with a problem in acoustics. More details on the Rayleigh distribution can be found in Johnson et al (1994) and references therein.The Rayleigh distribution has the following probability density function (pdf) and the cumulative distribution function (cdf), respectively,Weighted distributions are employed mainly in research associated with reliability, bio-medicine, meta-analysis, econometrics, survival analysis, renewal processes, physics, ecology and branching processes which are found in Patil and Rao (1978), Gupta and Kirmani (1990), Gupta and Keating (1985), Oluyede (1999), Patil andOrd (1976) and Zelen and Feinleib (1969). A weighted form of Rayleigh distribution has been published by Reshi et al (2014).…”
mentioning
confidence: 99%
“…Recently, Bergeron et al [3], Shen et al [4], Qin and Shen [5] and Ning et al [6] studied analysis of covariates under biased sampling. Studies on lengthbiased sampling can be traced as far back as Wicksell [7], Fisher [8], Neyman [9], Cox and Lewis [1], Zelen and Feinlein [2] and Patil and Rao [10]. An updated review of the subject can be found in Asgharian et al [11].…”
Section: Introductionmentioning
confidence: 99%